Combined solar energy converter - Antoshchenko, V.S.; Francev, Yu.V.; Lavrishchev, O.A.; Antoshchenko, E.V. (Recent Contributions to Physics, 2018)
A new design of a combined solar energy converter is proposed, which provides for increasing the efficiency and reliability of the device, as well as reducing its weight and cost. This is achieved by filling the working chamber with a liquid that is inert to the structural elements in contact with it, thus protecting the exposed surface of the solar cells from the atmosphere and preventing their degradation during operation. In addition, unlike conventional methods for protecting solar cells in photoconverters, for example, by lamination with EVA film, which degrades during operation, degrading the electrical characteristics of the photoconverter and can not be replaced by a new one, the use of a heat transfer fluid allows replacing it with reduced transparency. The combination of the optical properties of the liquid used makes it possible to increase the electrical efficiency of the device due to high transparency in the visible region of the spectrum and to reduce losses by light reflection from the back surface of the front plate. The use of a coolant with a high absorption in the infrared region of the spectrum makes it possible to efficiently store thermal energy and then transfer it to a heat exchanger. The corrosion resistance test of the transducer parts, including solar cells, was carried out for 2 years and did not reveal a deterioration in the device performance. A prototype of a combined solar energy converter was produced a peak electrical power of 25W and thermal power of 80 W under standard conditions.